The influence of teaching methods on creative problem finding. (June 2017) - Jia, Xiaojuan; Hu, Weiping; Cai, Fengchun; Wang, Haihong; Li, Jing; Runco, Mark A.; Chen, Yinghe
Graphical abstract: Highlights: Both short- and long–term classroom teaching process are designed to explore the impact of different teaching methods on primary school students Creative Problem Finding. A combination of two teaching methods is created and tested. The mixed teaching showed the strongest improvements in students flexibility and originality on the problem finding tasks, than lecture- and inquiry- teaching. Abstract: Problem finding is an important component of creativity, but research on it does not offer much guidance to teaching. The present research takes a step in that direction with two investigations. The first was a between-subjects evaluation of a short-term classroom teaching process, using creative Chinese problem finding (CCPF) to assess the impact. The second was a long–term, mixed-design of creative scientific problem finding (CSPF) as it developed in response to teaching that emphasized problem finding. Results showed that there were improvements, but different teaching methods had varied impact on students' creative problem finding (CPF) performance. A mixed teaching method that included both lecture- and inquiry-based teaching was superior to the lecture-based or inquiry-based methods when used separately. The mixed teaching showed the strongest improvements in students' flexibility and originality on the problem finding tasks. Finally, there was a significant interaction between teaching methods and instructional type (opened, closed) in flexibility and originality of CPF. Practical implications and limitations are discussed.